Serotype distribution of plasmid-encoded virulence profiles, and identification of espP and subAB alleles in verotoxigenic escherichia coli - Sanso, Andrea Mariel (2014)
Aims: This study was designed to characterize verotoxigenic Escherichia coli (VTEC), important food-borne pathogens, in relation to virulence genes found in large plasmids harboured by diseaseassociated strains. Our aim was to detect these genes and possible combinations of them, and to establish if some kind of relationship exists between these profiles and different serotypes. Study Design: Amplification of genes and allelic variants by PCR. Place and Duration of Study: Laboratorio de Inmunoquímica y Biotecnología (FCV-UNCPBA, Argentina), between June 2010 and July 2013. Methodology: 208 VTEC isolates belonging to 49 serotypes were characterized for the presence of plasmid-encoded genes: epeA (serine-protease), espP (extracellular serine protease) and its variants, katP (periplasmic catalase-peroxidase), stcE (zinc metalloprotease) and subA (subtilase cytotoxin) and its variants. Results: The most frequently detected gene was espP (87%), followed by ehxA (47%), saa (20%) and katP (17%), whereas epeA, subA and stcE ranged from 7 to 12%. Taking into account these genes, twelve profiles were observed, ranging from the presence of zero to five of the genes. Some serotypes presented only one plasmid profile whereas others, such as O20:H19, showed up to four different profiles. Functional differences have been previously found among EspP subtypes, and we found that several VTEC isolated from bovines or foods contained the espPα, which is one of the alleles possibly associated with severe human disease. Considering subtilase cytotoxin gene subtypes, only subAB1 was identified. Conclusion: Our results show that VTEC strains can possess different combinations of plasmidencoded virulence genes and even strains belonging to the same serotype can differ in relation to their plasmid genetic composition. In relation to allelic variants, LEE-positive serotypes showed for espP gene the allele α or the γ, and the detected subAB allele differed from the prevalent allelic variant subAB2 carried by strains circulating in sheeps and humans in European countries.